(untitled) (Bangladesh Journal of Zoology, 2024)
From September 2021 to August 2022 a study was carried out to assess the species diversity and abundances of pollinators and plant-pollinator interactions in Puthia Upazila of Rajshahi District, Bangladesh. A total of 3284 individuals were recorded, in which 109 species of 87 genera were identified as belonging to 49 families and 12 orders under three classes (Insecta, Aves and Mammalia). The relative abundance of insects and non-insect pollinators was 91.57% and 8.43%, respectively. A maximum of 32 species (relative abundance, RA= 32.70 %) was observed in the order Lepidoptera and minimum in the order Chiroptera (1 species; RA= 0.09 %). The most abundant family was Apidae (n= 267, RA= 8.12%) and the most dominant species was Eurema hecabe (n= 95, RA= 2.89%) (Family: Pieridae, Order: Lepidoptera). Based on number of individuals (n), the status of pollinators: 25 species were very common, 29 species were common, 18 species were fairly common, 21 species were rare and 16 species were very rare. A total of 51 flowering plants were documented that were visited by the pollinators, of which 32 were crop plants and 19 were non-crop flowering plants. Among them, the flowers of Orangeberry (Glycosmis pentaphylla) received the greatest number of pollinator species, i.e., 55. Overall, 79 species of recorded pollinators visited non-crop flowering plants, 65 species visited crop plants, and 35 species were common in both. According to the obtained individuals, the Shannon (H’) and Simpson (1-D) diversity indices were 4.41 and 0.99, respectively. The Berger-Parker dominance (d) and Pielou’s evenness index (J’) were 0.03 and 0.94, respectively, while the Margalef (DMg) and Menhinick (DMn) species richness indices were 13.34 and 1.90, respectively. The present study is the first report to offer baseline abundance and diversity of main pollinator groups in agroecosystems and provide data for a checklist of the variety of pollinators in the Puthia Upazila, Rajshahi, Bangladesh. Bangladesh J. Zool. 51(3): 267-287, 2023